Concept-mapping as a teaching method to facilitate critical thinking in nursing education: A review of the literature - Mary Chabeli (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2010)
Nursing students are exposed to a vast amount of information and reading material that is very specific, technical, and new to the students. Unless nurse educators provide a learning environment that promotes understanding through interaction, students might only commit unassimilated information to their short-term memory through rote learning, and no meaningful learning will occur. Nursing students must be able to link learned facts, concepts and principles with new knowledge in order to make sound rational decisions in practice (All & Havens 1997:1210, 1213). The aim of this paper is to describe the utilisation of concept-mapping as a teaching method to facilitate critical thinking by students in nursing education. The description of the utilisation of concept-mapping is done from the theoretical framework of concept-mapping and critical thinking to provide the epistemological basis for concept-mapping (Facione 1990:6, 13). Based on the exploration and description of the theoretical frameworks, four steps to facilitate critical thinking were formulated through concept-mapping on the basis of the educational process: the identification, interactive constructing process, formulation and evaluation steps. It is concluded that the utilisation of these steps will assist nurse educators to implement conceptmapping as a teaching method to facilitate critical thinking by student nurses in nursing education. Recommendations are made.